Prognostic value of systemic inflammation response index in patients with glioma: a meta-analysis - Jiang, Yizhen; Zhou, Lin (Frontiers in Immunology, 2025)
BackgroundThe systemic inflammation response index (SIRI) has been investigated for its prognostic relevance in patients with glioma; however, findings remain inconsistent. Therefore, this meta-analysis aimed to clarify the prognostic value of SIRI in glioma.MethodsPubMed, Web of Science, Embase, Cochrane Library, and CNKI were systematically searched through December 28, 2024. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to assess the association between SIRI and glioma prognosis.ResultsA total of 10 studies including 1,942 participants were analyzed. Elevated SIRI was significantly associated with poorer overall survival (OS) (HR=1.67, 95% CI=1.46–1.91, p<0.001) and shorter progression-free survival (PFS) (HR=1.80, 95% CI=1.29–2.52, p=0.001). Subgroup analyses indicated that the prognostic value of SIRI for OS and PFS was consistent regardless of sample size, pathological subtype, cutoff value, or type of survival analysis (p<0.05). Sensitivity and publication bias analyses confirmed the robustness of the results.ConclusionThis meta-analysis demonstrates that high SIRI is a significant predictor of OS and PFS in patients with glioma. SIRI may serve as a promising prognostic biomarker in glioma-related clinical practice.